Re-design of Prestress Structures Tiu Suntuk Dam Bridge - Alifia Syadira Tasyah; Zainuddin Husainy; Hermansyah; Adi Mawardin (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2023)
The existence of bridges is very important in supporting the mobilization and movement of people from one place to another so that proper bridge planning is needed so that human movement can be carried out safely and comfortably. Tiu Suntuk Dam Bridge has a span of 25.00 m with a width of 7.00m. This prestressed bridge is the main access to the Tiu Suntuk Dam area. Therefore, this bridge must have the strength towithstand large loads due to the high intensity of vehicle mobilization through the bridge. The re-planning of the upper structure of the Tiu Suntuk Dam Bridge uses SNI 1725: 2016 for loading on bridges and RSNI T-12-2004 concrete structure planning for bridges. In the replanning of the upper structure of the Tiu Suntuk Dam Bridge, it can receive self-load loading of 22.1416 kN/m, additional dead load of4.8420 kN/m,